Isolated and fermented orange and grape wastes: Bromatological characterization and phytase, lipase and protease source - Camargo, Dafne Angela [UNESP]; Pereira, Milene Stefani [UNESP]; dos Santos, Andressa Genezini [UNESP]; Fleuri, Luciana Francisco [UNESP] (Elsevier, 2022)
The aims of this study were to evaluate the bromatological characterization of isolated and fermented crude orange and grape wastes, and to investigate the presence and activities of phytase, lipase and protease in them. Fermented wastes accounted for better ash (until 49%), crude protein (around 40%) and fiber content (≤ 51%) results than the isolated ones (extracted directly from wastes, without fermentation). Overall, phytases enzymatic activity in isolated wastes, without the fermentation step, was up to 20 times higher than that in fermented wastes, which showed the same specific activity in the analysis - isolated orange bagasse reached 2436 U/mg of specific activity of phytases. Proteases presented the same profile as phytases, since their isolated waste showed enzymatic activity 69% higher than that of fermented waste, with emphasis on the total protein results recorded for mixed grape wastes, which evidenced difference up to 45 times higher than that of fermented orange wastes. Lipases did not show any activity in hydrolyzing fatty acids of intermediate chain, p-NPL (p-nitrophenyl laurate); however, both orange and grape wastes presented greater activities in hydrolysis of long-chain, p-NPP (p-nitrophenyl palmitate) and short-chain, p-NPB (p-nitrophenyl butyrate) fatty acids. Lipases in isolated orange bagasse showed the highest specific activity rate: 63% different from mixed grape wastes, which represented the second highest value recorded for this parameter.
Keywords: Agro-industrial waste; Aspergillus niger; Bromatological characterization; Citrus sinensis; Enzymes; Vitis vinifera